Is family history a predictor of response to tumour necrosis factor inhibitors in spondyloarthritis? A Swedish nationwide cohort study. (2nd January 2022) - Morin, M; Hellgren, K; Lindström, U; Frisell, T
Abstract : Objective : To determine whether a family history of spondyloarthritis (SpA) is associated with clinical presentation at the start of tumour necrosis factor inhibitor (TNFi) treatment, or predictive of TNFi drug survival and treatment response in patients with SpA. Method : Family history of SpA in patients with ankylosing spondylitis (AS), psoriatic arthritis (PsA), and undifferentiated SpA (uSpA) from the Swedish Rheumatology Quality register starting a TNFi as their first biologic in 2006–2018 was assessed through national registers. Clinical characteristics at treatment start were compared by family history status. We used Cox regression to estimate hazard ratios for drug discontinuation, and analysed treatment response at 3 and 12 months with linear regression. Multiple imputation was used to address missing data. Results : We included 9608 patients. Patients with family history had an earlier age at onset and longer disease duration at TNFi treatment start, but did not differ regarding disease activity and presence of SpA manifestations. Hazard ratios for drug discontinuation were 1.08 [95% confidence interval (CI) 0.89–1.31] for AS patients with a family history of AS, 1.02 (95% CI 0.89–1.18) for PsA patients with a family history of PsA, and 1.11 (95% CI 0.85–1.45) for uSpA patients with a family history of uSpA, after adjusting for demographic, socioeconomic, and SpA-related factors. Treatment response at 3 and 12 months was similar between groups. Conclusion : Family history of SpA was not found to be associated with clinical presentation at the start of TNFi treatment, nor was it associated with drug survival or treatment response in SpA patients starting a first TNFi.